Biosynthesis of Plant Triterpenoid Saponins: Genes, Enzymes and their Regulation - C.A. Yendo, Anna; de Costa, Farnanda; T. Da Costa, Cibele; C. Colling, Luana; Gosmann, Grace; G. Fett-Neto, Arthur (Mini-Reviews in Organic Chemistry, 2014)
Saponins are ubiquitous plant natural products, essentially involved in plant defense against biotic stresses, with numerous pharmaceutical and agricultural applications. The common precursor for triterpenoid saponins is squalene (30 carbon molecule) which, via cationic intermediates, is oxidized to 2,3-oxidosqualene. After cyclization, the basic triterpenoid cyclic structure undergoes oxidation by monoxygenases and glycosylations of hydroxyl groups. Chemical synthesis of saponins essentially recapitulates the main biosynthetic steps. However, to date, plants are the most viable source of these molecules. Jasmonic or salicylic acid, as well as their respective methylated derivatives, are important signaling molecules in the responses culminating in triterpenoid saponin production. The current challenges to improve triterpenoid saponin production include a better understanding of the signal transduction pathways leading to their accumulation (with emphasis on late enzymes and “master” regulatory transcription factors), isolation and heterologous expression of biosynthetic genes, and structural and modeling studies of biosynthetic enzymes and their catalytic mechanisms.
Keywords: enzymes